2013
DOI: 10.1109/surv.2012.111412.00160
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum Decision in Cognitive Radio Networks: A Survey

Abstract: Spectrum decision is the ability of a cognitive radio (CR) to select the best available spectrum band to satisfy secondary users' (SUs') quality of service (QoS) requirements, without causing harmful interference to licensed or primary users (PUs). Each CR performs spectrum sensing to identify the available spectrum bands and the spectrum decision process selects from these available bands for opportunistic use. Spectrum decision constitutes an important topic which has not been adequately explored in CR resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
149
0
19

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 286 publications
(174 citation statements)
references
References 83 publications
1
149
0
19
Order By: Relevance
“…" Spectrum Decision in Cognitive Radio Networks: A Survey" [35] => An overview of CRNs is presented. => Spectrum assignment in CRNs is discussed.…”
Section: Taxonomy Of Spectrum Access Methods and Authorisation Rmentioning
confidence: 99%
See 1 more Smart Citation
“…" Spectrum Decision in Cognitive Radio Networks: A Survey" [35] => An overview of CRNs is presented. => Spectrum assignment in CRNs is discussed.…”
Section: Taxonomy Of Spectrum Access Methods and Authorisation Rmentioning
confidence: 99%
“…In [35] and [36], the authors provide a comprehensive survey of challenges related to the spectrum decision/assignment in CRNs, including spectrum characterisation process and primary-system activity modelling, spectrum selection, and reconfiguration.…”
Section: A) Review Of the State-of-the-art (Sota) Survey Articlesmentioning
confidence: 99%
“…Deciding on the best spectrum band among the available bands under the QoS requirements of the applications is referred to as spectrum decision [8], [67]. In the first step of spectrum decision, statistical PU information and local readings from CRs are used to characterise each band (spectrum characterisation).…”
Section: A Spectrum Decisionmentioning
confidence: 99%
“…6. Spectrum selection is influenced by the underlying CRN topology [67]. In centralised, infrastructure based CRNs with a point-to-multipoint topology the spectrum selection is normally performed at the base station (BS) or access point (AP).…”
Section: ) Spectrum Selectionmentioning
confidence: 99%
“…Several survey papers exist in the literature in the context of CR communications covering a wide range of areas such as spectrum occupancy measurement campaigns [8], Spectrum Sensing (SS) [9]- [13], spectrum management [14], emerging applications [15], spectrum decision [16], spectrum assignment [17], spectrum access strategies [18], resource allocation [19], [20], machine-learning techniques [21] and CR networks [22]. However, to the best of authors' knowledge, no contributions have been reported in the direction of providing a comprehensive review of the existing CR approaches considering practical imperfections.…”
Section: Introductionmentioning
confidence: 99%